Math, asked by adityakp95, 4 months ago

Factorize the following:-

(1) (x − 3y)^3 + (3y − 7z)^3 + (7z -x)^3

I want answer from BrainlyDrug.​

Answers

Answered by aryans01
0

(x-3y)³+(3y-7z)³+(7z-x)³

=x³-27y³-3(x)(3y)(x-3y) + 27y³-343z³ -3(3y)(7z)(3y-7z) + 343z³ -x³ -3(7z)(x)(7z-x)

= -9xy(x-3y) -63yz(3y-7z) -21zx(7z-x)

= -9x²y+27xy²-189y²z+441yz² -147xz²+21x²z

=(-9x²y+21x²z)+(27xy²-189y²z)+(441yz²-147xz²)

= -3x²(3y-7z)+27y²(x-7z)+147z²(3y-x)

= -3[x²(3y-7z) -9y²(x-7z)-49z²(3y-x)]

Hope it is helpful.

Similar questions